Postprocessing Imaging Techniques of the Computed Tomography Angiography in Trauma Patients for Preprocedural Planning - Sutphin, Patrick D.; Baliyan, Vinit (Seminars in Interventional Radiology, 2021)
Computed tomography provides a wealth of diagnostic information in the trauma patient including the presence of organ, bone, and vasculature injuries for the rapid triage of trauma patients. In the context of interventional radiology, appropriately protocoled studies can be reviewed for vascular injury and help focus the angiographic assessment of bleeding patients to ideally achieve earlier hemostasis. This article outlines various image-processing techniques such as multiplanar reformats, curved planar reformats, maximum intensity projections, and volume rendering to identify and more thoroughly characterize vascular injuries as a preprocedural planning tool to expedite endovascular hemostasis in a case-based format.
Keywords: trauma; computed tomography; imaging; radiology; vascular injury; interventional radiology